Colony-stimulating factor 3 receptor (CSF3R) M696T mutation does not impact on clinical outcomes of a Ph+ acute lymphoblastic leukemia patient. Issue 3 (7th July 2021) - Chen, Xin; Wang, Bichen; Pang, Aiming; Yuan, Weiping; Jiang, Erlie; Chu, Yajing; Feng, Sizhou; Han, Mingzhe
Abstract : Abstract: Colony-stimulating factor 3 receptor (CSF3R) mutations have been identified in a variety of myeloid disorders. Although CSF3R point mutations (eg, T618I) are emerging as key players in chronic neutrophilic leukemia/atypical chronic myelogenous leukemia, the significance of rarer CSF3R mutations is unknown. Here, we report a 32-year-old female who was diagnosed as Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph + ALL) with the CSF3R M696T mutation and was undergone unrelated donor hematopoietic stem cell transplantation. The patient achieved complete remission with chemotherapy in combination with tyrosine kinase inhibitor (TKI) and long-term survival by unrelated donor transplantation. Meanwhile, we performed a series of experiments using murine interleukin 3 (IL-3)-dependent Ba/F3 cell line to evaluate the transforming capacity of the CSF3R M696T mutation. We confirmed the presence of a CSF3R M696T germline mutation in this patient which was inherited from her mother. The in vitro experiment results showed that the CSF3R M696T mutation contributes marginally to the tumor transformation of Ba/F3 cells, indicating that CSF3R M696T mutation was neutral in tumor transformation ability. We concluded that TKI is effective in patients with the CSF3R M696T mutation in Ph + ALL and donors with CSF3R M696T mutation might still be selected as the candidate for transplantation.